Enhanced rates of enzymatic saccharification and catalytic synthesis of biofuel substrates in gelatinized cellulose generated by trifluoroacetic acid - Tânia M. Shiga; Weihua Xiao; Haibing Yang; Ximing Zhang; Anna T. Olek; Bryon S. Donohoe; Jiliang Liu; Lee Makowski; Tao Hou; Maureen C. McCann; Nicholas C. Carpita; Nathan S. Mosier (Biotechnology for Biofuels, 2017)
Abstract Background The crystallinity of cellulose is a principal factor limiting the efficient hydrolysis of biomass to fermentable sugars or direct catalytic conversion to biofuel components. We evaluated the impact of TFA-induced gelatinization of crystalline cellulose on enhancement of enzymatic digestion and catalytic conversion to biofuel substrates. Results Low-temperature swelling of cotton linter cellulose in TFA at subzero temperatures followed by gentle heating to 55 °C dissolves the microfibril structure and forms composites of crystalline and amorphous gels upon addition of ethanol. The extent of gelatinization of crystalline cellulose was determined by reduction of birefringence in darkfield microscopy, loss of X-ray diffractability, and loss of resistance to acid hydrolysis. Upon freeze-drying, an additional degree of crystallinity returned as mostly cellulose II. Both enzymatic digestion with a commercial cellulase cocktail and maleic acid/AlCl3-catalyzed conversion to 5-hydroxymethylfurfural and levulinic acid were markedly enhanced with the low-temperature swollen cellulose. Only small improvements in rates and extent of hydrolysis and catalytic conversion were achieved upon heating to fully dissolve cellulose. Conclusions Low-temperature swelling of cellulose in TFA substantially reduces recalcitrance of crystalline cellulose to both enzymatic digestion and catalytic conversion. In a closed system to prevent loss of fluorohydrocarbons, the relative ease of recovery and regeneration of TFA by distillation makes it a potentially useful agent in large-scale deconstruction of biomass, not only for enzymatic depolymerization but also for enhancing rates of catalytic conversion to biofuel components and useful bio-products.